Purification of GTPgammaS binding proteins from membranes of porcine brain using convective interaction media (CIM) supports - Bavec, Aljoša (Acta chimica slovenica, 2000)
Membranes from porcine brain bind relatively large quantities of guanosine 5ć-(3-0-thio) triphosphate (GTPgammaS), a poorly-hydrolysable analogue of GTP.Chrotnatography of solubilized proteins with 1% Sodium cholate using CIM DEAE column (Convective Interaction Media) revealed two fractions reach in GTPgammaS binding proteins. In reduced SDS-PAGE analysis only these two fractions showed a protein band with molecular mass 42 kDa which corresponded to alpha subunits Gs Gi or G11. Comparison between CIM DEAE and traditional DEAE-Sephacel methods showed that membrane bound heterotrimeric G - proteins might be isolated by HPLC using CIM supports on second or minute time scale.
Keywords: HPLC; izolacija; proteini; separacijski procesi